Heritabilitas Produki Telur Ayam Lokal Papua Berbeda Genotip dari Lokus 24- bp Insertion-Deletion dalam Promotor Gen Prolaktin: Heritability of Egg Production in Papua Local Chickens Different Genotypes of 24- bp Insertion-Deletion Locus in Promotor Prolactin Gene - Muhammad Affan Mu'in; Sintje Lumatauw (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2021)
The heritability (h2) of a trait shows phenotypes variance of the trait caused by additive genetic variance. The h2 value is used to estimate the quantitative trait breeding value of livestock in order to improve these traits through selection. This study aims to estimate the h2 of egg production characteristics in Papua local chickens with different genotypes from the 24-bp InDel (Insertion-Deletion) locus in the prolactin gene promoter region (24-bp InDel/cPRLp locus). A total of 13 pairs of Papua local chickens consisting of 3 pairs of II genotypes (♂II x ♀II) and 11 female offspring, 5 pairs of ID genotypes (♂ID x ♂ID) and 19 female offspring, and 5 pairs of DD genotypes (DD x ♀DD) and 17 female offspring were used in this study. Observations were made on the characteristics of egg production in female offspring of each genotype group. The variance component for h2 estimation is obtained by the one-way analysis of variance method and the separation of the variance components for single pairs. The results showed that the h2 at first laying of eggs in all genotype groups was moderate (0.10 to 0.30); the h2 of the number of eggs produced from the time they first laid eggs until the age of 240 days in II and ID genotype groups was high (> 0.3), while in the DD genotype group was classified as moderate (0.10 to 0.30); and the h2 of egg weight in all genotype groups was moderate (0.10 to 0.30). The high h2 of a trait indicates that the trait is more dominated by additive genes and is more responsive to the selection treatment.